Assessment of Chestnut Gall Toughness: Implications for a Biocontrol Agent - Chiara Ferracini; Cristina Pogolotti; Simone Giacosa; Eleonora Vittoria Fontana; Luca Rolle; Alberto Alma (Insects, 2022)
(1) Torymus sinensis, the biocontrol agent of the Asian chestnut gall wasp Dryocosmus kuriphilus, is univoltine, but in NW Italy a small percentage of individuals exhibits a prolonged diapause, mainly as late instar larva. (2) In 2020, the diapause was investigated to evaluate its trend over the years. Due to the low survival rate of diapausing T. sinensis adults, the seasonal variation in the galls’ toughness was evaluated, thus assuming that dry galls over time can negatively affect emergence. The window of vulnerability of the gall wasp galls was also evaluated in controlled conditions. (3) The results showed that the average number of second year T. sinensis emerging per 100 cells was 0.41 ± 0.05, and dead adults accounted for 4.1 ± 0.23 per 100 cells. Gall toughness resulted in lower values for galls collected in May and June, and then gradually increased over time. In general, no difference was detected in the wall toughness of galls formed during the previous year when compared to current-year dry galls. Oviposition was recorded on all the tested galls collected in May and June, and no difference in the number of oviposition events was detected. Conversely, no oviposition was observed in July. Comparing the number of oviposition events by T. sinensis and the gall toughness, a negative correlation was found (R2 = −0.99). (4) The present findings contribute descriptive information on this gall’s structural traits, and the influence on gall wasp management is also discussed.